The risk factors of colistin methanesulfonate associated nephrotoxicity - TİGEN, ELİF (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2016)
Purpose: The risk factors of colistin methanesulfonate (CMS) associated nephrotoxicity are important. Our study attempts look into the prevalence of CMS-associated nephrotoxicity in Intensive Care Units (ICUs), and related risk factors. Materials and Methods: The study was conducted between September 2010 and April 2012 on 55 patients who underwent CMS treatment. Nephrotoxicity risk was defined based on the Risk Injury Failure Loss End-stage kidney disease criteria. Results: Fifty-five patients included in the study. A total of 22 (40%) patients developed nephrotoxicity. The correlation was detected between nephrotoxicity and patients over 65 with a high Acute Physiologic Assessment and Chronic Health Evaluation (APACHE) II score. APACHE II score was revealed an independent risk factor for nephrotoxicity. Conclusion: Advanced age and a high APACHE II score are significant risk factors in the development of nephrotoxicity at ICUs following CMS use. Patient selection and close monitoring are critical when starting CMS treatment.
Keywords: Colistin methanesulfonate; nephrotoxicity; risk factors; COHORT; SODIUM